Nurses' Knowledge of Cancer-Related Fatigue and the Coverage of This Subject in Nursing Training: A Cross-Sectional Study - WAGNER, Anna S.; MILZER, Marlena; SCHMIDT, Martina E.; KIERMEIER, Senta; MAATOUK, Imad; STEINDORF, Karen (The Journal of Nursing Research, 2025)
Background: Although cancer-related fatigue has a major impact on daily functioning and quality of life of patients, it remains underestimated in cancer care. Nurses play a significant role in multidisciplinary approaches to fatigue care. Purpose: This study was designed to investigate knowledge and attitudes among nurses regarding cancer-related fatigue and its management in daily clinical practice and training to suggest future actions for improvement. Methods: A cross-sectional design and an online questionnaire were used to assess nurses' perceived knowledge and self-efficacy, knowledge of guidelines and treatment options, and related coverage in education and training and to suggest how to improve training. The link to the study survey was distributed to cancer nurses working in Germany via mailing lists of randomly selected hospitals and rehabilitation centers, professional nursing associations, and social media. Data were analyzed descriptively as well as using the Mann-Whitney U test. Logistic regression analyses were conducted to identify variables linked to fatigue-related knowledge. Results: Nurses participating in the study were mainly working in certified cancer care institutions (70.1%). More than one-third of the 184 participants felt rather poorly or very poorly informed and reported low self-efficacy in counseling. Although working in certified institutions was found to increase the likelihood of accurately recalling the fatigue-related guidelines (OR = 6.24, 95% CI = [1.71, 22.74], p ＜ .01), few of the participants in this study knew any. Despite this, the majority was aware of the empirical evidence supporting physical activity (92.4%), yoga (79.9%), psychotherapeutic interventions (76.7%), mindfulness-based interventions (69%), and exercise (60.3%). Recommendation rates were heterogeneous. Those participants working in certified institutions were more likely to know about the empirical evidence related to exercise (OR = 3.03, 95% CI = [1.49, 6.18], p ＜ .01), which was positively associated with both recommending exercise and self-assessing one's subjective knowledge as high. Cancer-related fatigue is addressed minimally in basic nursing training and moderately (30.4%) to comprehensively (29.9%) in advanced nursing training. The participants suggested various strategies to improve related training. Conclusions/Implications for Practice: Most of the participants work in certified institutions but lack guidelines-related knowledge. Nevertheless, the participants had a fairly good awareness of interventions effective in reducing fatigue. However, awareness of the empirical evidence for exercise as one of the most promising treatment options was relatively low. Based on these findings, guidelines-oriented training is needed to strengthen related knowledge, particularly regarding self-efficacy in counseling in nurses. Awareness of this frequent sequelae should be raised early during basic nursing training and be covered comprehensively in advanced oncology nursing training. In general, the role of nurses within multidisciplinary teams in fatigue care needs to be determined to enable effective collaboration.